Systematic characterization of polycrystalline silica–carbonate helices. Issue 33 (5th August 2016) - Nakouzi, Elias; Knoll, Pamela; Hendrix, Kenzie B.; Steinbock, Oliver
Abstract : Biomorphs are complex, life-like structures that emerge from the precipitation of barium carbonate and amorphous silica in alkaline media. Abstract : Biomorphs are complex, life-like structures that emerge from the precipitation of barium carbonate and amorphous silica in alkaline media. Despite their inorganic nature, these microstructures have non-crystallographic morphologies such as helices and cardioid sheets. At the nanoscale, biomorphs arrange thousands of crystalline nanorods as hierarchical assemblies that resemble natural biominerals suggesting novel approaches towards the production of biomimetic materials. We report the synthesis of silica–carbonate biomorphs in single-phase, gradient-free solutions that differ markedly from the typical solution–gas or gel–solution setups. Our experimental approach significantly increases the duration of biomorph growth and hence assembles networks in which individual helices extend to several millimeters. These unusually long biomorphs allow the first quantitative measurements of mesoscopic parameters such as the helix wavelength, period, width, and linear as well as tangential growth velocities. We find that the latter quantities are system-specific and tightly conserved during many hours of growth. Moreover, the average double helix wavelength of (19 ± 3) μm and width of (9.6 ± 0.8) μm vary by less than 12% when the initial carbonate concentration is changed by three orders of magnitude. We also delineate the single helix growth mechanism and report the occurrence of ribbon-like structures and highly regular "superhelices". Our experiments clearly demonstrate the robustness and consistency of biomorph growth under stable chemical conditions.